Synthesis of pyridyl carbyne complexes and their conversion to N-heterocyclic vinylidenes. Issue 100 (29th November 2019) - Frogley, Benjamin J.; Hill, Anthony F.
Abstract : A new synthetic approach to hetero-aryl substituted carbyne complexes has allowed the synthesis of pyridyl functionalised carbynes and bis(carbynes), alkylation of which affords the first N-heterocyclic vinylidene complexes. Abstract : A new synthetic approach to hetero-aryl substituted carbyne complexes has allowed the synthesis of pyridyl functionalised carbynes and bis(carbynes), alkylation of which affords the first N-heterocyclic vinylidene complexes.